Application of Quality Function Deployment Method for Tourism's City Branding Analysis - Mardiyana, Eva; Zakiah, Siti; Gusnadi, Dendi (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to measure how much influence West Bandung Regency Tourism's City Branding has on the perceptions of tourists who will visit West Bandung Regency tourism using the Quality Function Deployment (QFD) method. City branding is an important marketing strategy in promoting tourist destinations. This study uses QFD as a tool to analyze the relationship between aspects of city branding and tourist perceptions to improve visiting decisions. The research method involves collecting data through surveys of tourists who have visited West Bandung Regency as well as content analysis of various marketing and branding materials used by local governments and related institutions. Data was analyzed using QFD techniques to determine the relationship between branding elements and tourist needs and preferences. The research results are expected to show that the elements in Tourism's City Branding in West Bandung Regency have a significant influence on tourist perceptions. Aspects such as destination image, tourism promotion, facilities and tourist experience are the main factors influencing tourists' decisions to visit West Bandung Regency. The implication of this research is the importance of local governments and other stakeholders in strengthening city branding as an effort to increase tourist visits and advance the regional tourism sector